Implementation of the Abortion Act: Report on a Year's Working of Abortion Clinics and Operating Sessions - Buckle, A. E. R. (1972)
The results of the first year's working of abortion clinics and operating sessions are reported. Seventy-eight per cent. of patients were managed on the basis of day admission and 20% were able to leave the hospital within four hours, operation having been carried out by either Karman catheter or by Bierer suction curette under paracervical block. These results were possible because of quick reference of patients to the clinics and the absence of delay in admission for operation. The measures detailed go some way towards managing the abortion problem within the hospital service; similar arrangements could be instituted elsewhere by the responsible regional hospital boards.